2015
DOI: 10.4049/jimmunol.1500463
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Allospecific NK Cell Tolerance Hinges on Instructive Allorecognition through the Activating Receptor during Development

Abstract: Little is known about how the prenatal interaction between NK cells and alloantigens shapes the developing NK cell repertoire towards tolerance or immunity. Specifically, the effect on NK cell education arising from developmental co-recognition of alloantigens by activating and inhibitory receptors with shared specificity is uncharacterized. Using a murine prenatal transplantation model, we examined the manner in which this seemingly conflicting input affects NK cell licensing and repertoire formation in mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
(40 reference statements)
1
7
0
Order By: Relevance
“…These authors have homed in on the NK arm of the innate immune system and have identified a subset of early NK cells within the fetal liver that express adult levels of alloreactive receptors, suggesting that NK cells may pose a barrier to engraftment of transplanted cells as early as the end of the first trimester in humans. Furthermore, this same group has shown that depletion of NK cells from the fetus, but not from the mother, enables reliable engraftment of allogeneic cells following IUTx 108 , 109 , 111 and that the levels of early chimerism required to induce NK cell tolerance agree exactly with the threshold levels discussed earlier. In a more recent study, this same group has provided data supporting a mechanistic link between the induction of prenatal NK cell tolerance and the process of trogocytosis, explaining how levels of engraftment of only 1–2% could result in exposure of donor antigens to a sufficient number of NK cells to reliably induce donor-specific tolerance.…”
Section: Barriers To Iutx Successsupporting
confidence: 63%
See 1 more Smart Citation
“…These authors have homed in on the NK arm of the innate immune system and have identified a subset of early NK cells within the fetal liver that express adult levels of alloreactive receptors, suggesting that NK cells may pose a barrier to engraftment of transplanted cells as early as the end of the first trimester in humans. Furthermore, this same group has shown that depletion of NK cells from the fetus, but not from the mother, enables reliable engraftment of allogeneic cells following IUTx 108 , 109 , 111 and that the levels of early chimerism required to induce NK cell tolerance agree exactly with the threshold levels discussed earlier. In a more recent study, this same group has provided data supporting a mechanistic link between the induction of prenatal NK cell tolerance and the process of trogocytosis, explaining how levels of engraftment of only 1–2% could result in exposure of donor antigens to a sufficient number of NK cells to reliably induce donor-specific tolerance.…”
Section: Barriers To Iutx Successsupporting
confidence: 63%
“… 107 Elegant recent work from Shaaban et al . 108–111 has indicated that NK cell tolerance appears to play a key part in establishing this engraftment threshold.…”
Section: Experimental Studies With Iutxmentioning
confidence: 99%
“…This is most evident with the observation that engraftment or rejection may occur in alternating littermates exposed to the same maternal influence (10, 11). The rejection may occur within the first few weeks after birth or may follow months of decay in the chimerism level whereas parallel transplantation in a naturally tolerant congenic strain combination revealed remarkably stable engraftment in nearly all recipients even at the lowest chimerism levels Furthermore, rejection in the allogenic recipients was complete with no detectable chimerism and normalization of the alterations in host lymphocyte populations that are typically seen even in the setting of microchimerism In our laboratory, this pattern was found to be independent of a potential maternal immune response as the rate of rejection was unaffected by the use of naïve foster dams and no maternal cells have been detected anywhere within the recipient mice after birth(11, 28, 29). A detailed assessment of the transplanted offspring revealed that engraftment or rejection in littermates correlated with a level of initial chimerism greater than or less than 1.8% of circulating cells (chimerism threshold).…”
Section: Evidence Supporting a Fetal Immune Response To Iuhctmentioning
confidence: 75%
“…The identification of the chimerism threshold as a reliable predictor of engraftment suggested that NK cell education was essential to durable NK cell tolerance. Subsequent experiments led to the characterization of a sophisticated process for prenatal NK cell allospecific education akin to thymic T-cell selection that resulted in the elimination of alloreactive (hostile) phenotypes from the mature pool of NK cells in stable chimeras (28, 29). In this process, NK cells that expressed allospecific activating Ly49 receptors without co-expression any of the allospecific Ly49 inhibitory receptors were deleted or rendered functionally anergic.…”
Section: Evidence Supporting a Fetal Immune Response To Iuhctmentioning
confidence: 99%
See 1 more Smart Citation